Răspuns :
[tex]a) \frac{1}{15} + (- \frac{5}{6}) + \frac{1}{9} = \frac{1}{15} - \frac{5}{6} + \frac{1}{9} = \frac{6 - 75 + 10}{90} = \frac{ - 59}{90} = - \frac{59}{90} [/tex]
[tex]c)0,2 + ( \frac{13}{4} - 3 \frac{1}{4}) + ( - 1,2) = 0,2 + \frac{13}{4} - \frac{3 \times 4 + 1}{4} - 1,2 = 0,2 + \frac{13}{4} - \frac{13}{4} - 1,2 = 0,2 - 1,2 = - 1 [/tex]
[tex]c)0,2 + ( \frac{13}{4} - 3 \frac{1}{4}) + ( - 1,2) = 0,2 + \frac{13}{4} - \frac{3 \times 4 + 1}{4} - 1,2 = 0,2 + \frac{13}{4} - \frac{13}{4} - 1,2 = 0,2 - 1,2 = - 1 [/tex]
![Vezi imaginea Trombolistul](https://ro-static.z-dn.net/files/d7a/d0c7301ccb3eda8c242d796afe88f9ee.jpg)